Kedudukan Akta Hibah Bagi Anak Angkat Dari Pemberian Harta Orang Tua Angkat (StudiPutusan Nomor: 1637/Pdt.G/2019/Pa.Jp) - Nur Indah Utami; Ferryani Krisnawati; Suryati (Wijayakusuma Law Review, 2023)
The purpose of this research is to find out the position of the deed of grant made by a notary which contains grants fromadoptive parents to their adopted children. To achieve this goal the authors use a normative juridical approach. Datasources are secondary data as the main data which includes primary legal materials, secondary legal materials and tertiarylegal materials. The data obtained were analyzed qualitatively. Conclusion: Based on the results of research and discussionregarding the position of the deed of grant made by a Notary for adopted children, normatively, the Deed of Grant Number19/2008 dated 28 April 2008 made before Notary Jhonni M Sianturi, SH is valid and has legal force, because it has fulfilledthe requirements in the grant agreement both formally and materially. The strength of proof of a notarial deed as a meansof proof is the perfect strength of proof, because the privilege of an authentic deed lies in the strength of the proof. Anauthentic deed gives the parties and their heirs or people who have rights from it a perfect proof. An authentic deed has thepower of proof in such a way that it is considered attached to the deed itself, meaning that an authentic deed is bindingevidence because what is written in the deed must be considered true and trusted by the judge. An authentic deed also hasperfect evidentiary strength because it does not require the addition of other evidence, in other words, an authentic deedhas outward, formal and material evidentiary strength in accordance with the provisions under Article 1886 of the CivilCode. A notarial deed as an authentic deed has external, formal and material evidentiary power, if a notary deed is drawnup according to the applicable provisions, then the deed will be binding on the parties as an authentic deed and includes thecourt which must accept the notary deed as perfect evidence